A biocompatible electrochemical sensor based on PtNi alloy nanoparticles-coupled N-GQDs for in situ monitoring of dopamine in glioma cells. (January 2023) - Panda, A.K.; Murugan, K.; Sakthivel, R.; Dhawan, U.; Lin, L.-Y.; Duann, Y.-F.; He, J.-H.; Chung, R.-J.
Abstract: We report the design and construction of enzyme-free sensor using platinum–nickel (PtNi) bimetallic alloy nanoparticle-conjugated nitrogen-doped graphene quantum dots (N-GQDs) for the highly specific in situ monitoring of dopamine (DA) secreted by glioma cells (C6). PtNi@N-GQDs nanocomposites were synthesized using a simple ultrasonication method. The resulting hybrid material was an excellent electrocatalyst for the redox activity of DA owing to the combined properties of PtNi alloys and highly conductive N-GQDs. The PtNi@N-GQDs-based sensing platform demonstrated substantial sensing ability with a detection range of 0.0125–952 μM, a sensitivity of 0.279 μA/μM/cm 2, and a limit of detection of 0.005 μM (S/N = 3). The sensing performance of PtNi@N-GQDs was highly stable, selective, and reproducible. We successfully showed the practical application of the PtNi@N-GQDs sensor by quantifying DA in the blood serum and human urine samples. Finally, we used the PtNi@N-GQDs biocompatible platform to quantify DA released from C6 cells. Graphical abstract: Image 1 Highlights: We developed an enzyme-free dopamine electrochemical sensor using PtNi@N-GQDs nanocomposites. It demonstrated a linear detection range of 0.0125–952 μM μM, and a limit of detection is 0.005 μM. Practical applicability was verified in human urine and blood serum samples. Real-time quantification of dopamine released from C6 cell line was performed.